PHILIPPINES-THAILANDINDONESIA EXPLORATION: Recontextualizing Anti-SLAPP in Protecting Access to Ecological Justice - Syahruddin, Erwin; Andre Cardenas Jr.; Akbar Sarif; Rahmat Saputra (Universitas Negeri Semarang, 2025)
This study examines the strategic challenges faced by environmental rights defenders in Indonesia, the Philippines, and Thailand, including the abuse of the law through the practice of Strategic Lawsuits Against Public Participation (SLAPPs) used by corporations or authorities to silence public criticism of environmental damage. Although all three countries have legal instruments for protection, their implementation is still limited and does not comprehensively cover aspects of procedural law. This study uses a normative legal approach with a comparative legal method to analyze the form of anti-SLAPP legal protection and its potential integration into the criminal procedural system. The results show that Indonesia and the Philippines still limit legal protection to environmental issues, while Thailand has more advanced normative provisions but has not been effective in preventing SLAPPs at the early stages of the legal process. A legal mechanism is needed that allows for the termination of SLAPP cases at the investigation or prosecution stage through clear legal indicators and strengthening prosecutorial discretion based on the principle of public interest. The novelty of this study lies in the proposed integration of Anti-SLAPP principles into criminal procedural law as a preventive measure against the criminalization of environmental activists and as a recognition of ecological justice, where protection of public participation and freedom of expression is an integral part of social justice in the context of environmental protection.